Estudio comparativo del proceso de compostaje tradicional y mediante lombrices californianas (Eisenia foetida) en la degradación de residuos urbanos - Velarde Pintag, Mishell Alexandra (2026)
The accumulation of agricultural and market waste is a priority environmental challenge in Riobamba, where the lack of sustainable alternatives limits its utilization. Among available techniques, composting and vermicomposting are emerging as viable strategies for converting waste into organic fertilizers. In this context, the present research compared both processes to determine which is more efficient at degrading organic waste. Corn stalks and fruit-and-vegetable residues supplemented with bovine manure were used, adjusting the carbon-to-nitrogen (C:N) ratio to 26.95 using the Tchobanoglous equation. The study was conducted in the Yaruquíes parish (El Shuyo neighborhood) under an experimental design with two treatments, each with three replicates, and an initial substrate of 90 kg per pile. Key parameters—temperature, moisture, and pH—were monitored for three months. In addition, physicochemical analyses were performed in both treatments to determine organic matter, total nitrogen, phosphorus, potassium, calcium, magnesium, electrical conductivity, and pH. The results showed that vermicomposting with Eisenia “fetida” remained under stable mesophilic conditions (20–25 °C) with a moisture content of 70–80%, while traditional composting reached thermophilic temperatures of up to 55 °C and exhibited greater variability in moisture (45–60%). A higher content of total nitrogen, organic carbon, and calcium was also observed in the vermicompost compared with the compost. Furthermore, the physicochemical results of the compost and vermicompost were compared with the technical and regulatory ranges established by the Council of the European Union (Regulation (EU) 2019/1009) and the US Composting Council (USCC), and several parameters were found to be close to the minimum reference limits.